Investigating the modelling of psychological wellbeing according to self-expression and selfefficiency in high school students of Imam Khomeini Relief committee - Maleki, Mansoureh; Maleki, Fatemeh; Mirzayi, Somayyeh; Farasati, Roshanak (The Turkish Online Journal of Design Art and Communication, 2016)
Present research has investigated the psychological well-being modelling based on the self-expression and self-efficiency in the high school students of the Imam Khomeini Relief Committee (RA). The aim of this research is to provide a model with a proper fitness. The research method is correlationaldescriptive. The statistical population of this research consists of high school students of Relief Committee studying in the academic year 93-94. A sample of 300 individuals was selected from the statistical population of 1,200 individuals. For collecting data, were used three questionnaires of Reef’s psychological well-being, Scherrer’s self-efficiency and Gambrill and Ritchie’s selfexpression. The reliability and validity of questionnaires have been confirmed by using the Cronbach's alpha. For analyzing data, descriptive tests (variation range, mean and standard deviation) and structural equation model (LISREL) were used. Data analysis shows that the self-expression had a significant and positive effect on self-efficiency and self-efficiency has a significant and positive effect on self-expression. Self-expression has a significant and positive effect on the psychological well-being.
Keywords: Self-Expression; Psychological Well-Being; Self-Efficiency; Imam Khomeini Relief Committee (RA); Kendini İfade Etme; Psikolojik İyilik Hali; kendine Verimlilik; İmam Humeyni Yardım Komitesi (RA)